2022
DOI: 10.1111/1744-9987.13930
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of all renal replacement therapy modalities in terms of COVID‐19 infection rate & mortality in the COVID‐19 pandemic and importance of home therapies

Abstract: Background This study aimed to compare the infection rate and infection‐related mortality among all renal replacement therapies during the COVID‐19 pandemics. Methods One thousand three hundred thirty‐six end‐stage renal disease (ESRD) patients who had applied for renal replacement therapy between March 2020 and January 2021 were included in the study. COVID‐19 infection and mortality rates were compared between patient groups. Results The CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
0
1
Order By: Relevance
“…A greater number of patients in the HD group had a longer RRT duration. These factors may be related to higher COVID-19 hospitalization and mortality rates in patients on HD, and this result correlates with those of previous studies [13,14]. As relatively older patients with multiple comorbidities and those admitted to nursing hospitals tend to undergo HD rather than KT or PD, COVID-19 hospitalization and mortality rates are commonly highest in patients who underwent HD.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A greater number of patients in the HD group had a longer RRT duration. These factors may be related to higher COVID-19 hospitalization and mortality rates in patients on HD, and this result correlates with those of previous studies [13,14]. As relatively older patients with multiple comorbidities and those admitted to nursing hospitals tend to undergo HD rather than KT or PD, COVID-19 hospitalization and mortality rates are commonly highest in patients who underwent HD.…”
Section: Discussionsupporting
confidence: 85%
“…As patients who underwent HD visit the dialysis center multiple times a week, they might have the highest risk considering the contagious nature of COVID-19. Previous studies conducted in other countries reported that patients on in-center HD showed the highest incidence of COVID-19 among RRT modalities [13,14]. However, in our analysis, patients who underwent HD had a lower incidence of COVID-19 than those who underwent KT.…”
Section: Discussioncontrasting
confidence: 77%
“…The mortality rate for the cohort was 2.87% ( n : 39), with higher rates observed in center hemodialysis (CHD) at 3.87% ( n : 33), kidney transplant (Tx) at 1.47% ( n : 5), and peritoneal dialysis (PD) at 0.81% ( n : 1). The COVID‐19 infection rate among patients receiving home replacement therapy (HRT) ( n : 39) was significantly lower than that of those undergoing center hemodialysis (CHD) ( n : 139) ( P < 0.001) [58].…”
Section: Discussionmentioning
confidence: 99%